Evasion of the Serving of a Criminal Punishment - A. A. Urusov (Сибирское юридическое обозрение, 2019)
The article deals with the issues related to the study of the practice of execution of criminal penalties without isolation of convicts from society. Special attention is paid to the analysis of problems of definition of malicious evasion from punishment serving. Within the article various points of view of scientists stated in the special literature concerning the legal nature of the studied problem are investigated, activity of criminal and Executive inspections and judicial practice about replacement of an unserved part of punishment by a more severe type of punishment to maliciously evading from serving criminal sentences without isolation of condemned from society is analyzed. The General criteria of malicious evasion from serving of punishment are revealed, the point of view of need of an exception of concept of “malicious evasion” from the criminal and criminal executive legislation is formulated, having left only “evasion from serving of punishment” and to fix in the criminal code signs of this evasion. It is offered to criminalize cases of evasion from punishment serving, as independent structure of crime with purpose of new punishment.